Implementation effectiveness evaluation of watershed ecological compensation policy for sustainability based on the Huai river Basin in China - Xue, Kaijia; Yang, Yingjian; Huang, Zhiyi (Frontiers in Environmental Science, 2024)
Watershed ecological compensation (WEC), as a public policy for sustainability, aims at balancing the ecological environment and economic development within specific watersheds to achieve the harmonious coexistence between humans and nature. This study takes an innovative approach by constructing an effective WEC policy evaluation model for the Huai River Basin based on a comprehensive evaluation system and empirical research. By systematically integrating the fuzzy comprehensive evaluation of the analytic hierarchy process and descriptive statistical methods, the model provides a comprehensive evaluation of the WEC policy's influence on the basin's overall environment. The results indicate that each area related to the Huai River Basin presents a positive promotion of the ecological environment and economic development based on its comprehensive score calculated by the model. Besides, the results also reveal a noticeable reduction in major pollution elements in the Huai River Basin based on empirical research of the model, accompanied by effective improvements in water and air quality. However, the impact of WEC's policy implementation on regional economic development is relatively limited. It is found that although the WEC's policy implementation is in a favorable state, downstream cities of the Huai River Basin still exhibit a phenomenon of "free-riding". Meanwhile, the WEC's policy overlooks the focus on economic concerns and lacks robust legal safeguards. Therefore, this study further proposes constructive recommendations, including promoting collaborative governance between upstream and downstream areas, balancing environmental protection and economic development, and improving the legal system for the WEC.